Lymphoepithelioma-Like Carcinoma of the Salivary Gland: Is Radiotherapy Alone Adequate? - Orit Kaidar-Person; Abraham Kuten; Salem Billan (Case Reports in Otolaryngology)
Introduction. Lymphoepithelioma-like carcinoma (LELC) of the salivary gland is a rare tumor. Currently, surgery with or without radiotherapy is the recommended treatment for all salivary gland carcinomas. However, in contrast to other high-grade salivary gland carcinomas, LELCs are considered radiosensitive. There are only a few published reports of radiotherapy alone for the treatment of salivary gland LELC. Case. We present two cases of LELC of the salivary gland. One was treated with surgery and postoperative radiotherapy, and the other was given a single cycle of chemotherapy and then radiotherapy. Currently, both patients have no evidence of disease. Conclusion. Radiotherapy as a single modality should be reevaluated. The role of systemic chemotherapy to gain systemic control should be addressed due to noteworthy metastatic disease.